Design Warehouse Management Inventory System Based On The Website - Ririn Restu Aria; Indra Riyana Rahadjeng (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2018)
Warehouse management system is one of the most important parts of manufacturing companies in order to monitor all the supplies owned by the company for incoming goods and goods out. PT. Arista Latindo, is still using manual way to know the inventory they have today, so it will take a lot of time to be able to process the results of the use of raw materials, the resulting production, when using the system there are many mistakes that often occur in the process of recording thus affecting the overall system. Therefore, with technological advances to improve the existing system from the manual will be converted into computerized. For making these applications can use the website as a form of view that can be accessed by administrators more easily, quickly and effectively. When the design is done to better understand the needs of the user, the process is done and the output to be used, the testing process is done by waterfall method and black box testing method to check the errors associated with the display in applications that have been made and will be used in the company.